2000
DOI: 10.1027//1015-5759.16.3.202
|View full text |Cite
|
Sign up to set email alerts
|

Personality and Self-Rated Work Performance

Abstract: Summary: Data are reported on the correlation between the California Psychological Inventory (CPI) and self-ratings of work performance for 889 municipal employees. Overall, CPI scores do not correlate with self-rated general or technical proficiency, or effort. CPI scales that assess relations with others correlate modestly with self-ratings of leadership. CPI scales that assess attitudes, values and “character” correlate modestly with self-ratings of personal discipline. These results give some evidence of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…By considering effort exertion, we connect stress theory with resource theory to address this research gap. In accordance with previous studies that identified effort exertion as an invisible mechanism regulating individual efforts and work performance (e.g., Brown and Peterson, 1994;Brown and Leigh, 1996;Cook et al, 2000), our findings measuring presenteeism over different timeframes clarify how individuals allocate their limited effort capacity to work activities and how this allocation leads to different outcomes. Overall, by incorporating time into a processbased model, our framework offers a more nuanced treatment of presenteeism.…”
Section: Discussionsupporting
confidence: 91%
“…By considering effort exertion, we connect stress theory with resource theory to address this research gap. In accordance with previous studies that identified effort exertion as an invisible mechanism regulating individual efforts and work performance (e.g., Brown and Peterson, 1994;Brown and Leigh, 1996;Cook et al, 2000), our findings measuring presenteeism over different timeframes clarify how individuals allocate their limited effort capacity to work activities and how this allocation leads to different outcomes. Overall, by incorporating time into a processbased model, our framework offers a more nuanced treatment of presenteeism.…”
Section: Discussionsupporting
confidence: 91%
“…However, since our subjects’ job categories were incommensurable, objective criteria of performance did not exist across categories, making subjective criteria more comparable. Precedent for this usage is drawn from past literature ( Cook, Young, Taylor, & Bedford, 2000 ; Dabke, 2014 ). Further, interaction effects are less likely to be subjected to common method effects ( Podsakoff et al, 2003 ) and the main effects of both variables have been established in past literature ( Ashforth et al, 2008 ; Edwards, 2008 ; Jansen & Kristof-Brown, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…These results implied that the amount of alcohol adolescents drank had no predictive value for peer-perceived sociability one year later and that also the class context did not alter this association. Finally, we also tested possible curvilinear associations between individual-level alcohol use and sociability by classifying adolescents as abstainers (i.e., never had drunk alcohol), occasional drinkers (Cook et al, 1998;Pape & Hammer, 1996;Reid, 1978;Silbereisen & Noack, 1988) or peer-reported sociability (Engels et al, 2006). These studies were not able to test any direction of effects.…”
Section: Multilevel Analysesmentioning
confidence: 97%
“…In addition, abstainers seem to be more submissive and dependent on others (Cook, Young, Taylor, & Bedford, 1998;Pape & Hammer, 1996). The theoretical assumption here is that alcohol use may facilitate adolescent psychosocial development.…”
Section: Introductionmentioning
confidence: 97%